(untitled) (Academicia Review-A Multidisciplinary Online Journal, 2026)
This article analyzes the theoretical and procedural foundations of considering labor disputes within civil proceedings. The author, relying on the norms of the Labor Code of the Republic of Uzbekistan, highlighted the features of individual and collective labor disputes. The study comparatively examines the experience of developed foreign countries (USA, Great Britain, Germany, and France) and reveals the advantages of labor tribunals, the principle of parity, and the stages of forced reconciliation. In conclusion, scientific proposals were put forward to improve national legislation.